RETRACTED: Approaches to assessing the digital maturity of an industrial enterprise - Babkin Alexandr; Mikhailov Pavel; Teplytsky Gleb; Ochilov Akram; Haiqi Ding (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001